A Rare Self-Limiting Adamantiades Behcet Diseasen in A Woman: A Case Report - Fajrin, Farah Meriana; Damayanti; Hidayati, Afif Nurul; Murtiastutik, Dwi Murtiastutik; Astindari, Astindari; Widyantari, Septiana; Sari, Maylita (Faculty of Medicine, Universitas Airlangga, 2024)
Background: Adamantiades–Behçet is a genetically determined disorder with a probable environmental triggering factor and is an inflammatory disease representing vasculitis. Chronic relapsing progressive course, Dapson prevents problems in other organs. Case Report: A 31-year-old woman with chief complaints of a progressive painful ulcer on her genitalia in the last month, covered by pus and with a bad odor, and also recurrent tongue sores that healed spontaneously. Multiple partner sexual intercourse, joint pain, and an eye complaint were denied. Her husband has no history of previous sexually transmitted diseases. The labia majora region showed a solitary ulcer, sharply marginated, and covered with pus. The Haemophilus ducreyi, pathergy, VDRL, TPHA, and rapid test HIV all came back negative. Enterococcus faecalis, found in bacterial culture, is sensitive to Penicillin and glycopeptide. Histopathologically recited vasculitis with thrombus in the blood vessel marks Behcet disease. The patient was given Mefenamic Acid (3x500mg), doxycicline (2x100 mg), and a wet dressing. The ulcer decreased in size after 3 weeks of treatment. Discussion: Adamantiades-Behçett disease is characterized by chronic, recurrent oral aphthous ulcers, genital ulcers, skin lesions, ocular lesions, and arthritis or arthropathy. Viral and bacterial infections have been implicated in initiating immunopathologic pathways. The pathergy test is pathognomonic, but it is not specific and often gives a negative result. Histopathological examination is still the best option to establish the diagnosis.